Autopercepção de saúde e qualidade de vida na perspectiva da pessoa idosa - Schirmer, Aline Faé (2023)
Aging is a physiological and heterogeneous process that is not necessarily accompanied by pain and illness, which can become an experience of awakening and maturation. Despite the above, many families tend to understand aging from a distorted perception, such as fragility and incapacity, which leads to loss of autonomy and reduced functionality. In view of this, we investigated the elderly person's perception of their health and quality of life with the aim of understanding them in aging, from the elderly person's perspective, through a look at themselves. This is a descriptive qualitative research with elderly people aged 60 to 76 years, of both sexes, assisted by the Specialized Rehabilitation Center of a city in the interior of Rio Grande do Sul. Data collection took place in March 2023 and the sample consisted of 16 people who answered a sociodemographic questionnaire and individual semistructured narrative interview, recorded in audio. The project was approved by the Research Ethics Committee of the Federal University of Santa Maria under opinion 5.911.222/2023 and CAAEE 65637922.2.0000.5346. The data were analyzed qualitatively based on Bardin's Content Analysis. With this study it was observed that quality of life and health are in unison and that they present pillars for aging well. These pillars are therapeutic and social groups, friendships and interpersonal relationships, access to health services, financial independence, work, family ties, faith and spirituality. The elderly people participating in the study understand health and quality of life from a similar perspective and realize that everyday issues are fundamental in understanding how to live well and that they go far beyond illnesses, challenges and declines.